FLORAE MALESIANAE PRAECURSORES XVI ON THE TAXONOMIC SUBDIVISION OF THE GLEICHENIACEAE, WITH DESCRIPTIONS OF NEW MALAYSIAN SPECIES AND VARIETIES - HOLTTUM, R. E. (Research Center for Biology, 1957)
A new subdivision is given of the fern family Gleicheniaceae. The genus Platyzoma R. Br is excluded from the family. The genus Stromatopteris from New Caledonia is arranged in a distinct subfamily. In the remainder of the family, subfamily Gleichenioideae, two genera are recognized, Gleichenia (with subgenera Diplopterygium, Gleichenia, and Mertensia) and Dicranopteris (with subgenera Acropterygium and Dicranopteris) . The problem of subdividing the family is discussed with reference to former treatments and to new data, and a conspectus of the new system, with synonymy and key to the genera and subgenera, is given. A number of new species, new varieties, and new combinations is made both in Gleichenia and Dicranopteris.